Dal'nii Vostok . Dal'nii Vostok . The Far East . Дальний Восток - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The public's understanding of the value of privatization vouchers; the Korean "Red Cross" help their countrymen in Russia; harvesting. Series description: The program consists of regional television reports of the Dal'nevostochnogo federal'nogo okrug [Far Eastern Federal District] of the Russian Federation. Ценность ваучеров в понимании населения, помощь "Красного креста" Кореи своим соотечественникам в России, уборка урожая. Описание серии: Программа состоит из репортажей регионального телевидения Дальневосточного федерального округа Росчсийской Федерации.